Crisis? What crisis? : The Callaghan government and the British 'winter of discontent' - Shepherd, John, 1942- (Book collections on Project MUSE., 2013)
Over thirty years later, the 'winter of discontent' of 1978-79 still resonates in British politics. On 22 January 1979, 1.5 million workers were on strike. Industrial unrest swept Britain in an Arctic winter. Militant shop stewards blocked medical supplies to hospitals; mountains of rubbish remained uncollected; striking road hauliers threatened to bring the country to a standstill; even the dead were left unburied. Within weeks, the beleaguered Callaghan Labour government fell from power. In the 1979 general election, Margaret Thatcher became Prime Minister, beginning eighteen years of unbrok.